Evaluation of the effects of ewe prolificacy potential and stocking rate on herbage production, utilization, quality and sward morphology in a temperate grazing system. (1st August 2017) - Earle, E.; McHugh, N.; Boland, T. M.; Creighton, P.
Abstract: This study investigated the effect of ewe prolificacy potential (PP; predicted number of lambs born ewe −1  year −1 ), stocking rate (SR; ewes/ha) and their interaction on herbage dry matter (DM) production, utilization, quality and sward morphology within a temperate grass‐based lamb production system. The study had a 2 × 3 factorial design, consisting of two ewe PP as dictated by sire breed (180 medium prolificacy potential (MP—Suffolk crossbred) and 180 high prolificacy potential ewes (HP—Belclare crossbred)) and three SR: low (LSR; 10 ewes/ha), medium (MSR; 12 ewes/ha) and high (HSR: 14 ewes/ha). Each treatment was managed in a rotational grazing system, with LSR, MSR and HSR treatments grazing to target post‐grazing sward heights (PGSH) of 4.55, 4.15 and 3.75 cm respectively. Herbage DM production (above target PGSH) and utilization were highest at the HSR, intermediate at the MSR and lowest at the LSR ( p  < .001). Ewe PP had no effect on herbage DM production, utilization, quality or sward morphology ( p  > .05). The proportion of leaf in the sward (above target PGSH) was 4% greater in MSR and HSR compared with LSR ( p  < .05). In conclusion, findings demonstrate the potential to support increased ewe PP through the selection of ewe genotypes of a genetically higher PP and lower mature live weight and increased SR within a temperate grass‐based lamb production system.